ATP-Sensitive Potassium Channels Exhibit Variance in the Number of Open Channels below the Limit Predicted for Identical and Independent Gating - Choi, Kee-Hyun; Licht, Stuart (PUBLIC LIBRARY SCIENCE, 2012)
In small cells containing small numbers of ion channels, noise due to stochastic channel opening and closing can introduce a substantial level of variability into the cell's membrane potential. Negatively cooperative interactions that couple a channel's gating conformational change to the conformation of its neighbor(s) provide a potential mechanism for mitigating this variability, but such interactions have not previously been directly observed. Here we show that heterologously expressed ATP-sensitive potassium channels generate noise (i.e., variance in the number of open channels) below the level possible for identical and independent channels. Kinetic analysis with single-molecule resolution supports the interpretation that interchannel negative cooperativity (specifically, the presence of an open channel making a closed channel less likely to open) contributes to the decrease in noise. Functional coupling between channels may be important in modulating stochastic fluctuations in cellular signaling pathways.
Keywords: ION CHANNELS; MEDIATED PHOSPHORYLATION; SUPERPOSITION PROPERTIES; ACETYLCHOLINE-RECEPTORS; NEGATIVE COOPERATIVITY; QUANTAL VARIABILITY; CELLS; MEMBRANE; CONDUCTANCE; PROTEINS